DEVELOPING A PUBLIC VOICE: PLACE-BASED EDUCATION AS AN APPROACH TO EDUCATION FOR SUSTAINABLE DEVELOPMENT IN THE EFL CLASSROOM - Ver Steeg, Jackson (PUPIL: International Journal of Teaching, Education and Learning, 2019)
This paper argues for developing education for sustainable development (ESD) as a specific focus area in the university EFL classroom, and suggests place-based education as a method to develop the attitudes and skills identified as critical to developing the discourse area of sustainability. This research aimed to determine whether engaging students with making connections between a local place of interest and personal identity stimulated personal agency within a global sustainable development (SD) discourse. Participants worked on group e-projects that asked them to identify a local place of importance, whether personal or civic, and redesign it with an aspect towards sustainability. Student attitudes regarding SD were gauged from pre-and post-testing using a modified version of the OECD’s Global Competency Self-Assessment Survey, as well as student interviews and reflective comments. Preliminary results suggest that these attempts to introduce sustainability into the classroom through place-based education improved awareness and attitudes about global issues, and positively impacted abilities to participate in the SD discourse community in English. This is notable, as the sustainable development discourse community is increasingly important to nearly all university students of English, regardless of intended career track, and is worthy of inclusion as a specific focus of study.